2020
DOI: 10.1111/jcmm.15410
|View full text |Cite
|
Sign up to set email alerts
|

Low levels of AMPK promote epithelial‐mesenchymal transition in lung cancer primarily through HDAC4‐ and HDAC5‐mediated metabolic reprogramming

Abstract: AMP‐activated protein kinase (AMPK) serves as a “supermetabolic regulator” that helps maintain cellular energy homeostasis. However, the role of AMPK in glucose metabolism reprogramming in lung cancer remains unclear. Here, our study shows that low AMPK expression correlates with metastasis and clinicopathologic parameters of non–small‐cell lung cancer. Low AMPK significantly enhances the Warburg effect in HBE and A549 cells, which in turn induces the expression of mesenchymal markers and enhances their invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Interestingly, low AMPK expression levels correlate with tumor grade, TNM stage, and lymph node metastasis. Low AMPK levels in human bronchial epithelial HBE cells are responsible for an increase in glycolytic flux (due to the induction of HK2 expression which, in turn, promotes EMT ( Figure 3 ) [ 170 ]. AMPK ↓ ⇒ HK2 ↑ ⇒ Glycolysis ↑ ⇒ EMT …”
Section: Emt and Metabolism In Selected Cancersmentioning
confidence: 99%
“…Interestingly, low AMPK expression levels correlate with tumor grade, TNM stage, and lymph node metastasis. Low AMPK levels in human bronchial epithelial HBE cells are responsible for an increase in glycolytic flux (due to the induction of HK2 expression which, in turn, promotes EMT ( Figure 3 ) [ 170 ]. AMPK ↓ ⇒ HK2 ↑ ⇒ Glycolysis ↑ ⇒ EMT …”
Section: Emt and Metabolism In Selected Cancersmentioning
confidence: 99%
“…As dysregulation of energy metabolism also contributes to EMT ( 76 ), it is possible that metabolic reprogramming is involved in HDAC5-mediated EMT. It was recently demonstrated that HDAC5 together with HDAC4 enhanced glycolysis by inducing the upregulation of hexokinase 2 (HK2), which was critical for EMT induced by hypoexpression of 5′ AMP-activated protein kinase (AMPK) in lung cancer ( 72 ).…”
Section: Hdac5 In Cancermentioning
confidence: 99%
“…Cell proliferation ability was determined using a Cell Counting Kit‐8 (CCK‐8; KeyGen Biotech) and a colony formation assay as previously reported 19 . Briefly, 5 × 10 3 cells were seeded in 96‐well plates, and recommended volume of CCK‐8 solution was added at 24, 48, 72 and 96 h, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The migration and invasion assays were performed as previously described 19 . For the migration assay, 4 × 10 4 H1299 cells or H292 cells were seeded in serum‐free medium in the upper chamber and incubated for 24 h at 37℃.…”
Section: Methodsmentioning
confidence: 99%